Arbuscular mycorrhizal fungi regulate amino acid metabolism, phytohormones and glycolysis pathway to promote the growth of Suaeda salsa under combined Cd and NaCl stresses - Jia, Bingbing (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.